Low Muscarinic Receptor Binding in Prefrontal Cortex From Subjects With Schizophrenia: A Study of Brodmann's Areas 8, 9, 10, and 46 and the Effects of Neuroleptic Drug Treatment - Crook, Jeremy M.; Tomaskovic-Crook, Eva; Copolov, David L.; Dean, Brian (The American journal of psychiatry, 2001)
OBJECTIVE: Aberrant cholinergic inputs and synaptic neurotransmission in the prefrontal cortex induce cognitive impairment, which is a central feature of schizophrenia. Postsynaptic excitatory muscarinic cholinergic M1 and M4 receptors are the major cholinoceptive targets in the prefrontal cortex and hence may be involved in the pathology and or pharmacotherapeutics of schizophrenia. METHOD: Using quantitative autoradiography, the authors analyzed the binding of the M1 M4 receptor selective antagonist [3H]pirenzepine in prefrontal cortex (Brodmann's areas 8, 9, 10, and 46) from schizophrenia patients who had (N=6) or had not (N=11) been treated with the anticholinergic agent benztropine mesylate and from normal comparison subjects (N=20). Moreover, preliminary studies of [3H]pirenzepine binding in rat frontal cortex following administration of antipsychotic drugs or benztropine mesylate were performed. RESULTS: Relative to those of comparison subjects, the mean levels of [3H]pirenzepine binding were significantly lower in Brodmann's areas 9 and 46 of the schizophrenia patients not treated with benztropine mesylate (18% lower in Brodmann's area 9 and 21% lower in Brodmann's area 46) and in all four examined regions of the patients who had received benztropine (51%-64% lower). Antipsychotic or anticholinergic drugs tended to increase or have no effect on the density of [3H]pirenzepine-labeled receptors in rat frontal cortex. CONCLUSIONS: Because M1 and M4 receptors are critical to the functions of prefrontal cortical acetylcholine, the present findings suggest a functional impairment in cholinergic neurotransmission in schizophrenia and the possibility that muscarinic receptors are involved in the pharmacotherapeutics of the disorder.